Nutritional content of infant commercial foods and formulas available in Iceland 2016 - Tinna Óðinsdóttir 1989- (2017)
Background and aims: The availability and selection of infant commercial foods and formulas in Iceland is constantly increasing. There are some doubts that infant commercial foods meet infants’ nutritional requirements or provide encouragement to develop their ability to eat food that suits their age. The objective of this thesis is to construct a database containing infant commercial foods and formulas on the Icelandic market in the autumn of 2016. Methods: Information on infant commercial foods and formulas (n=248) was collected by taking photos of product packaging or obtained from manufacturers’ websites. General information and nutritional content was listed in Microsoft Excel. 3-day weighing food records from the Iceage2 study were used to estimate consumption of infant commercial foods and formulas among Icelandic nine-month-old infants (n=25). Results: The market mainly consists of ready-made foods, with a 70% proportion of total, of which 44% were fruit puree. Most of the products were aimed at infants from 4+ months (29.4%) and 6+ months (34.3%), served in sachets or jars. The average energy content was lowest for the ready-made foods with a mean (SD) energy content of 63.3 (14.5) kcal per 100 g. Powdered meals were rich in energy and nutrients and were considered as sufficient complementary food. The mean consumption of infant commercial foods among Icelandic nine-month-old infants was 30% of their daily intake. Consumption of ready-made foods had the largest share (46.6%), of which consumption of fruit puree was highest (30.2%). Conclusion: The main purpose of complementary feeding is to provide enough energy and nutrients to fulfil infants’ requirements. The market mainly supplies ready-made foods that turned out to have the lowest energy content of all food groups and would not serve the intended purpose of enhancing the energy and nutrient density in infants’ diets. Yet, consumption of ready-made foods was the most common form of consumption. Bakgrunnur og markmið: Aðgengi og úrval af tilbúnum ...